2021
DOI: 10.1029/2020jc016591
|View full text |Cite
|
Sign up to set email alerts
|

Upper Ocean Stratification in the Eastern Pacific During the SPURS‐2 Field Campaign

Abstract: The region between a shallow mixed layer and a deep isothermal layer resulting from salinity stratification is called a barrier layer (BL). Since BLs hinder the surface heat and momentum exchange with the ocean subsurface, they play an important role in air‐sea interaction. Synoptic features and formation of BLs and associated temperature inversions (TIs) in the Eastern Pacific Fresh Pool (EPFP) were investigated using shipboard observations. BLs and TIs were found in the high‐precipitation EPFP, a frontal tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In any case, the model results suggest that stratification is dominant compared to rain forcing in modulating the salinity response to rain: when preexisting stratification is present, freshwater from rain is confined near the surface and slowly mixes downward. Preexisting stratification in the eastern tropical Pacific results from longer‐term freshwater input from the ITCZ and ocean dynamics (Bingham et al., 2020; Katsura & Sprintall, 2020; Katsura et al., 2021). Stratification is also produced locally by individual rain events (Iyer & Drushka, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, the model results suggest that stratification is dominant compared to rain forcing in modulating the salinity response to rain: when preexisting stratification is present, freshwater from rain is confined near the surface and slowly mixes downward. Preexisting stratification in the eastern tropical Pacific results from longer‐term freshwater input from the ITCZ and ocean dynamics (Bingham et al., 2020; Katsura & Sprintall, 2020; Katsura et al., 2021). Stratification is also produced locally by individual rain events (Iyer & Drushka, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ship‐based radar and in situ observations from SPURS‐2, which took place during 2016–2017 in the eastern tropical Pacific Ocean, show significant variations in the patterns of convective and stratiform rain (Rutledge et al., 2019; Thompson et al., 2019). As a result of rainfall, stratified layers were commonly observed near the surface during the SPURS‐2 field campaign (Bingham et al., 2020; Katsura & Sprintall, 2020; Katsura et al., 2021). Hence, a wide‐range of preexisting stratification conditions are present in this region (Figure 2e).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Akima spline has been used not only in oceanography (ex. Katsura et al, 2021;Oka et al, 2011;Sato et al, 2006), but also in wide scientific and engineering fields (Boor, 1978;Evenden, 1989). The potential temperature (θ) and potential density (σ θ ) were calculated from the interpolated values.…”
Section: Datamentioning
confidence: 99%
“…They attributed these thick BLs and associated TIs to southward Ekman advection, which transports cold and fresh water driven by northeastward winds. Katsura et al (2021) used the in-situ observations from a 2017 boreal autumn cruise and suggested that the sharp SSS front and surface flow are primary contributors to the formation 3 of 21 of the BLs and TIs in the NETP. A high-resolution model study focused on two specific thick BL events along 125°W and suggested a sharp salinity front tilt associated with vertical circulation as an additional mechanism for the NETP BLs (Bingham et al, 2020).…”
mentioning
confidence: 99%